Surface Design Options in Polymer- and Lipid-Based siRNA Nanoparticles Using Antibodies - Gabel, Michael; Knauß, Annkathrin; Fischer, Dagmar; Neurath, Markus; Weigmann, Benno (International Journal of Molecular Sciences, 2022)
The mechanism of RNA interference (RNAi) could represent a breakthrough in the therapy of all diseases that arise from a gene defect or require the inhibition of a specific gene expression. In particular, small interfering RNA (siRNA) offers an attractive opportunity to achieve a new milestone in the therapy of human diseases. The limitations of siRNA, such as poor stability, inefficient cell uptake, and undesired immune activation, as well as the inability to specifically reach the target tissue in the body, can be overcome by further developments in the field of nanoparticulate drug delivery. Therefore, types of surface modified siRNA nanoparticles are presented and illustrate how a more efficient and safer distribution of siRNA at the target site is possible by modifying the surface properties of nanoparticles with antibodies. However, the development of such efficient and safe delivery strategies is currently still a major challenge. In consideration of that, this review article aims to demonstrate the function and targeted delivery of siRNA nanoparticles, focusing on the surface modification via antibodies, various lipid- and polymer-components, and the therapeutic effects of these delivery systems.
CRIS-Team Scopus Importer:2022-12-09
Keywords: antibody; gene delivery; lipid nanoparticle; polymer nanoparticle; siRNA; surface-functionalized nanoparticles; targeted drug delivery

The Memory T Cell “Communication Web” in Context with Gastrointestinal Disorders—How Memory T Cells Affect Their Surroundings and How They Are Influenced by It - Knauß, Annkathrin; Gabel, Michael; Neurath, Markus; Weigmann, Benno (Cells, 2022)
Gut-related diseases like ulcerative colitis, Crohn’s disease, or colorectal cancer affect millions of people worldwide. It is an ongoing process finding causes leading to the development and manifestation of those disorders. This is highly relevant since understanding molecular processes and signalling pathways offers new opportunities in finding novel ways to interfere with and apply new pharmaceuticals. Memory T cells (mT cells) and their pro-inflammatory properties have been proven to play an important role in gastrointestinal diseases and are therefore increasingly spotlighted. This review focuses on mT cells and their subsets in the context of disease pathogenesis and maintenance. It illustrates the network of regulatory proteins and metabolites connecting mT cells with other cell types and tissue compartments. Furthermore, the crosstalk with various microbes will be a subject of discussion. Characterizing mT cell interactions will help to further elucidate the sophisticated molecular and cellular networking system in the intestine and may present new ideas for future research approaches to control gut-related diseases.
CRIS-Team Scopus Importer:2022-10-07
Keywords: colorectal cancer; Crohn’s disease; etrolizumab; IBD; immune cells; interactions; memory T cells; metabolites; microbiota; ozanimod; ulcerative colitis; vedolizumab

Tofacitinib Affects M1-like and M2-like Polarization and Tissue Factor Expression in Macrophages of Healthy Donors and IBD Patients. - Lethen, Isabelle; Lechner-Grimm, Kristina; Gabel, Michael; Knauß, Annkathrin; Atreya, Raja; Neurath, Markus; Weigmann, Benno (Inflammatory Bowel Diseases, 2024)
BACKGROUND: Tofacitinib, as inhibitor of Janus kinases (JAK), interrupts the transmission of numerous pro-inflammatory cytokines involved in the pathogenesis of inflammatory bowel diseases (IBD). Therefore, tofacitinib provides a potent option to treat ulcerative colitis (UC). Besides the anti-inflammatory potential, inhibition of widespread JAKs carries the risk of side effects. Macrophages are involved in the form of different subtypes in inflammation, wound healing, and even coagulation. This study aimed to explore the balanced use of tofacitinib in M1-like as well as M2-like macrophages of healthy donors and patients with IBD. METHODS: Monocytes of healthy donors and patients with chronic courses of IBD were obtained from blood samples. Macrophage colony-stimulating factor (M-CSF)-derived macrophages were treated with tofacitinib (1 µM, 5 µM, 10 µM) and polarized with either lipopolysaccharide and interferon (IFN)-γ towards M1-like-phenotype or with interleukin (IL)-4 towards M2-like-phenotype. ELISA and flow cytometry were used to evaluate cytokine levels and surface molecules. RESULTS: Tofacitinib had a modulating effect on M1-like macrophages whereby the effect on pro-inflammatory cytokines (TNF-α, IL-6, IL-1β, IL-12, IL-23) was less pronounced than the induction of anti-inflammatory IL-10. However, during M2-like polarization tofacitinib impaired the development of the corresponding phenotype becoming evident through decreased IL-10 levels and CD206 expression in treated macrophages. In both phenotypes, tofacitinib strongly downregulated the expression of immunostimulatory molecules (CD80, CD86, CD83, CD40). Furthermore, a dose-dependent correlation between treatment with tofacitinib and expressed tissue factor was noticed. CONCLUSIONS: Tofacitinib influences both polarizations (M1/M2) and the expression of tissue factor in a dose-dependent manner.
EVALuna2:550695